A evolução das vacinas anti-rábicas na Medicina Veterinária - Antunes, João Marcelo Azevedo de Paula; Allendorf, Susan Dora; Appolinário, Camila Michele; Peres, Marina Gea; Vicente, Acácia Ferreira; Fonseca, Clóvis Reynaldo Silva; Demoner, Larissa de Castro; Megid, Jane [UNESP] (My University, 2012)
Rabies is a zoonotic disease that is characterized by progressive character fatal encephalitis, found worldwide, except Antarctica. Few diseases such as rabies, have been the subject of many therapeutic attempts aimed at cure. Vaccination is considered the most efficient method for the control and prevention of infectious diseases in humans and animals. The objective of this study was to demonstrate the increasing development of rabies vaccines in Veterinary.

A raiva é uma doença zoonótica que se caracteriza por encefalite progressiva de caráter fatal, encontrada mundialmente, com exceção da Antártica. Poucas doenças, como a raiva, têm sido objeto de tantas tentativas terapêuticas visando a cura. A vacinação é considerada o método mais eficiente para o controle e prevenção das doenças infecciosas no homem e nos animais. O objetivo deste trabalho foi demonstrar o crescente desenvolvimento das vacinas antirrábicas na Veterinária.
The evolution of anti-rabies vaccines in veterinary medicine
Keywords: Rabies; Vaccine; Animals; Raiva; Vacina; Animais